Aspectos biológicos y procesos de biodegradación de residuos orgánicos de Hermetia illucens “mosca soldado” en el Fundó Almendra, Perú 2025 - Hidalgo Meléndez, Gerardo Andres (2025)
This study investigated the potential of Hermetia illucens to transform organic waste at the Almendra Farm, evaluating its biological aspects and biodegradation processes. Orange waste was collected and fermented, and the biological and reproductive aspects of Hermetia illucens were evaluated under controlled conditions to determine its biodegradation capacity. The study revealed an average copulation period of 25 minutes, an oviposition of 370 eggs/mass, and a total biological cycle of 57.6 days. Analysis of the orange peel and bagasse compost revealed a pH of (8.88-7.81) and contents of N (0.49%-4.04%), P (4.69%-12.61%), and K (4.3%-5.75%), respectively. These ranges are considered optimal for agricultural use. In conclusion, Hermetia illucens proved to be a viable and efficient alternative for organic waste management, producing high-quality fertilizer with the potential to improve agricultural sustainability in the region.